Development of decision support systems prototype for promotion in Service Corp Malaysian Army human resources management using simulation model / Hishamudin A. Rahim - A. Rahim, Hishamudin (2006)
Currently the system that caters for officer's promotion rank Leftenan to Kapten, Kapten to Mejar and Mejar to Leftenan Kolonel at Service Corp Directorate Human Resource Department is done by Merit System using Microsoft Excel. These Merit System is not a suitable tool because the decision makers who only have access to a generic decision tool would be difficult to make decision in order to analyze and recommend an action. This Decision Support System (DSS) Promotion System is built to select the officer's in Service Corp Malaysian Army who are qualified for promotion. The target users of this system are staff career department, Director of Service Corp and promotion board. This system is mainly focusing the development of DSS promotion in entering, updating data and selection the qualified officer's to promote rank. The DSS also focused on several criteria and weightage in order to produced the result. This system is developed using MS Visual Basic and MS Access is used as its database. This system has been successfully tested using the current data. It shows that this promotion system is able to produce the result and report for the decision makers to analyze and make decision accurately. Hopefully this system will aid the users for selection the qualified officer in promotion process.